TRANSFORMASI DAKWAH DIGITAL: PELATIHAN PEMBUATAN FRAME KONTEN DAKWAH DENGAN CANVA BAGI PENYULUH AGAMA ISLAM - Desi Puspita; Siti Aminah (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2026)
The development of digital technology has encouraged changes in the methods of delivering religious messages to the community. Islamic religious counselors are required to utilize digital media as a more effective and engaging means of communication in religious outreach. However, many counselors still have limitations in digital content creation skills. This community service activity aims to improve the digital competencies of Islamic religious counselors through training on creating digital content frames using Canva and CapCut applications. The methods used in this activity include socialization, practical training, and mentoring in designing digital da'wah content frames. The participants were Islamic religious counselors at the Kementerian Agama of Pagar Alam City. The results of the activity indicate that participants were able to understand the basic concepts of digital da'wah content design and create attractive content frames using Canva and CapCut. Furthermore, this activity enhanced participants' creativity and ability to utilize digital media as a medium for religious outreach. It is expected that through this training, Islamic religious counselors can optimize the delivery of religious messages to the community through more creative and communicative digital media..